Robert Patterson Hughes papers - Hughes, Robert Patterson, 1839-1909.
Correspondence, diaries, writings, printed memorial, biographical material, and photographs documenting Hughes's military career, including his account of the Battle of Little Bighorn written the following day as aide-de-camp to Gen. Alfred Howe Terry and material relating to his service during the Philippine insurrections (1898-1901).
U.S. Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Terry, Alfred Howe, -- 1827-1890.; United States. -- Army -- Officers; Little Bighorn, Battle of the, Mont., 1876.; Philippines -- History -- Revolution, 1896-1898.; Philippines -- History -- Philippine American War, 1899-1902.; Army officers